Pengaruh Pendidikan Kesehatan Terhadap Pemberian Asi Ekslusif Pada Ibu Yang Mempunyai Bayi Usia 7-12 Bulan - merlyna Suryaningsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Exclusive breastfeeding is breastfeeding asearly as possible after birth, given without eatingschedule and not given another, though only water,until the age of 6 months. Based on preliminarystudy found 70% of mothers do not give exclusivebreastfeeding. The purpose of this study to analyzethe effect of health education on exclusivebreastfeeding in mothers with infants aged 7-12months.The research used a retrospective analyticstudy time. Population of 40 mothers with infantsaged 7-12 months and samples taken 36 mothers.Sampling Probability sampling techniques usingsimple random sampling with sampling. Datacollection with a questionnaire on the independenthealth education and dependent variables exclusivebreastfeeding and using statistical test Chi-Square.The results of the 36 mothers with infants aged 7-12months nearly half of the respondents who do notget health education does not give exclusivebreastfeeding as many as 17 respondents (47.2%).For respondents who received health educationtends to give exclusive breastfeeding as many aseight respondents (22.2%). Statistical analysis of theresults of Chi-Square P Value obtained value (0.023)< α (0.05) so that H0 is rejected and Ha is accepted,there is the influence of health education onexclusive breastfeeding.Adding regular healtheducation in particular about giving exclusivebreastfeeding in mothers with infants aged 7-12months in order to understand and be able tounderstand about the benefits of exclusivebreastfeeding, so that henceforth will give exclusivebreastfeeding mothers to their babies